I supposed to integrate (x^2 + x)^(1/2).
I do it this way
int (x^2 + x)^(1/2) = x(x^2 + x)^(1/2) - 1/2* int (x(2x + 1))/(x^2 + x)^(1/2) = x (x^2 + x)^(1/2) - 1/2((xln(x^2 +x)) - ln(x^2 + x))
IF u now take 2pi ((x = 1) - (x = 0)) u are supposed to get
pi(6(2)^(1/2) - ln(3 + 2(2)^(1/2)) / 4
And i dont get it, so i wonder what im doing wrong.
Now i get 2*(((t^3)/3)*(t^2 + 1)^(1/2)) - (int) (((t^4)/3) * (1/(t^2 + 1)^(1/2)) = 2*(((t^3)/3)*(t^2 + 1)^(1/2)) - ((((t^4)/3) * ln(t + (t^2 + 1)^(1/2))) - (int) (4t/3)*ln(t + (t^2 + 1)^(1/2)))
I dont see where to go from my last step, becuse i dont the int of
ln(t + (t^2 + 1)^(1/2))and there got to be an easier way than finding out.